Respuesta :
Answer:
[TeX]x^2+y^2+4.8x+9.6y-16.2=0[/TeX]
Step-by-step explanation:
The equation of a circle centre(h,k) of radius r is given by:
r²=(x-h)²+(y-k)²
If radius, [TeX]r=\sqrt{45}[/TeX]
Centre, (h,k)=(-2.4,-4.8)
Substitution into the equation of the circle formula
r²=(x-h)²+(y-k)²
[TeX](\sqrt{45})^{2}=(x-(-2.4))^{2}+(y-(-4.8))^{2}[/TeX]
[TeX]45=(x+2.4)^{2}+(y+4.8)^{2}[/TeX]
[TeX]45=x^2+4.8x+5.76+y^2+9.6y+23.04[/TeX]
[TeX]0=x^2+y^2+4.8x+9.6y+5.76+23.04-45[/TeX]
[TeX]x^2+y^2+4.8x+9.6y-16.2=0[/TeX]
The equation of the circle is therefore given as:
[TeX]x^2+y^2+4.8x+9.6y-16.2=0[/TeX]
Answer:
(x + 2.4)^2 + (y + 4.8)^2 = 45
Step-by-step explanation:
Khan Academy